Directing Syntactic Traffic. (26th March 2020) - Sobin, Nicholas
Abstract: While much work in generative syntax has adopted bottom‐up syntactic derivation, a number of factors favor a top‐down approach. This article offers a new articulation of the top‐down Merge Right–Branch Right approach. In accord with the general Minimalist goals that computation should be carried out in small domains, that structure is based on binary pairings, and that grammatical mechanisms should, as far as possible, be limited to those that are logically necessary, three hypotheses are advanced: (i) that downward movement/copying of elements is driven by theta marking; (ii) that a [D] parameter operates across a range of syntactic constructions to direct displaced elements either through the syntactic structure or into a memory buffer to reach their points of selection/theta marking; and (iii) that the concept of the memory buffer previously proposed in the literature should be modified so that some but not all displaced elements enter it. The [D]‐parameter hypothesis offers a common basis for a variety of syntactic phenomena: short movement in expletive sentences, T‐to‐C movement in wh questions, the Comp–trace effect, and the anti‐Comp–trace effect seen in relative clauses.